Circular structure of values in preschool children - Cieciuch, Jan; Hulak, Agata; Kitaj, Mariola; Leszczyńska, Justyna; Bulkowska, Dorota (Studia Psychologica: Theoria et praxis, 2011)
The presented study is the first attempt to verify the Schwartz’s circular model of value structure in middle childhood. Previous studies have verified the model in adulthood and adolescence, and most recently - thanks to the method called Picture Based Value Survey by Döring (Döring et al., 2010) - even in late childhood. However, to date there was a lack of adequate testing methods for younger children. To verify the hypothesis of the circular structure of value in middle childhood, we have developed a method called the Puppet Values Interview, inspired by the Berkeley Puppet Interview (Measelle, Ablow, Cowan, Cowan, 1998). The study was conducted individually and 60 children aged from 4 to 6 years participated in it. Multidimensional scaling obtained from the results supported the hypothesis about the circular structure of values and the possibility of dividing the continuum into four higher order values: self-transcendence, selfenhancement, openness to change and conservation.